Association of Asprosin Levels in Metabolic Syndrome - Jayanti, Evy Tri; maria diah, pramudianti; Kunti Dewi Saraswati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Metabolic syndrome (MS) is a condition characterized by disruptions in the body's metabolism. The risk factors for MS are impacted by age, gender, body mass index (BMI), and low-density lipoprotein (LDL) to high-density lipoprotein (HDL) cholesterol ratio. Asprosin is a hormone protein secreted by white adipose tissue that stimulates oxidative stress and proinflammation, affecting changes in body metabolism that trigger the development of MS. To assess the relationship between serum asprosin levels, age, gender, BMI, and LDL/HDL cholesterol ratio on the incidence of MS where asprosin can be used as a single marker for predicting MS. An observational study with a cross-sectional approach was conducted at Dr. Moewardi General Hospital (RSDM) in Surakarta from November to December 2023, involving 85 consecutively sampled subjects. The population was selected based on inclusion criteria. Asprosin examination was performed using the Rayto RT 2100 instrument with the enzyme-linked immunosorbent assay (ELISA) method. Statistical analysis involved the use of the Kolmogorov-Smirnov test, followed by bivariate and multivariate analysis. There was a significant difference (p <0.001) between the MS and non-MS groups in terms of age, LDL/HDL cholesterol ratio, and asprosin variable. The mean serum asprosin level in the MS group was 25.81 (3.11-122.02) ng/mL. The cutoff value of asprosin was found to be >11.35 with a sensitivity of 83.3% and specificity of 79.1%. There was an association between serum asprosin levels, age, and LDL/HDL cholesterol ratio with the occurrence of MS. Further research is needed with a prospective cohort study design before and after the onset of MS.